2019
DOI: 10.1016/j.cca.2019.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical performance of three hand-held point-of-care creatinine analyzers for renal function measurements prior to contrast-enhanced imaging

Abstract: Background: As iodine-based contrast can cause deterioration of renal function in patients with impaired kidney function, guidelines advise to measure creatinine and calculate estimated glomerular filtration (eGFR) prior to administration. Point-of-care (POC) devices seem an attractive alternative to central laboratory testing but uncertainty regarding analytical and clinical comparability remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
3
11
0
4
Order By: Relevance
“…Studies that have used POC testing rely on a fingerprick for the POC device and venipuncture for laboratory testing. A study done in Nicaragua found POC testing for creatinine demonstrated acceptable repeatability, excellent sensitivity (100%) and modest specificity (79%) using blood samples from two different sources (forearm for Jaffe kinetic method with a Roche Cobas Integra 400 analyzer and fingerstick for POC) [26]. However, there are no available studies that compare the accuracy of solely using fingerprick capillary blood for comparable POC and IDMS results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have used POC testing rely on a fingerprick for the POC device and venipuncture for laboratory testing. A study done in Nicaragua found POC testing for creatinine demonstrated acceptable repeatability, excellent sensitivity (100%) and modest specificity (79%) using blood samples from two different sources (forearm for Jaffe kinetic method with a Roche Cobas Integra 400 analyzer and fingerstick for POC) [26]. However, there are no available studies that compare the accuracy of solely using fingerprick capillary blood for comparable POC and IDMS results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, significant bias has been reported between the creatinine measured on Nova StatSensor and routine laboratory enzymatic methods [ 16 , [19] , [20] , [21] , [22] , [23] ]. The StatSensor and the iSTAT, have been reported to exhibit a bias in creatinine of +16% and +6% respectively against the routine laboratory analyzers [ 5 ]. Thus, biases in creatinine measurement have been shown across different POCT devices compared with other POCT or routine laboratory analyzers.…”
Section: Discussionmentioning
confidence: 99%
“…The epoc® Blood Analysis System (Siemens Healthineers, Oakville, Ontario, Canada) is a relatively newer, portable, point-of-care (POCT) device and has recently been compared to various other POCT, blood gas, and hematology instruments [ [1] , [2] , [3] , [4] , [5] ]. This system is comprised of credit card-sized test cards and a wireless card reader.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing the performance of the i-STAT device to other platforms have been inconsistent. 35 , 36 , 37 , 38 One study showed that the i-STAT overestimated creatinine results by 3.88 µmol/L in comparison to the Roche enzymatic creatinine results. This overestimation occurred predominantly at higher creatinine concentrations.…”
Section: Discussionmentioning
confidence: 99%